2021
DOI: 10.3390/biomedicines9030299
|View full text |Cite
|
Sign up to set email alerts
|

Development and Carcinogenesis: Roles of GATA Factors in the Sympathoadrenal and Urogenital Systems

Abstract: The GATA family of transcription factors consists of six proteins (GATA1-6) that control a variety of physiological and pathological processes. In particular, GATA2 and GATA3 are coexpressed in a number of tissues, including in the urogenital and sympathoadrenal systems, in which both factors participate in the developmental process and tissue maintenance. Furthermore, accumulating studies have demonstrated that GATA2 and GATA3 are involved in distinct types of inherited diseases as well as carcinogenesis in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…GATA factors, like other transcription factors, function in conjunction with other coregulators, including deacetylases, methyltransferases, and acetyltransferases, to confer specific patterns of gene regulation. 56 GATA3, one of the transcription factors that binds to GATA-containing sequence DNA, targets via two zinc-finger domains. 57 Current evidence indicates that TGF-β negatively regulates GATA3 expression.…”
Section: ■ Discussionmentioning
confidence: 99%
“…GATA factors, like other transcription factors, function in conjunction with other coregulators, including deacetylases, methyltransferases, and acetyltransferases, to confer specific patterns of gene regulation. 56 GATA3, one of the transcription factors that binds to GATA-containing sequence DNA, targets via two zinc-finger domains. 57 Current evidence indicates that TGF-β negatively regulates GATA3 expression.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Analysis of the action of neuroblastoma PHOX2b variants in developing sympathetic neurons demonstrated their stimulatory effect on neuroblast proliferation combined with dedifferentiation indicating routes to malignancy modulated by PHOX2b in combination with HAND2 (Reiff et al 2010 ). Studies for other transcription factors of the network directing sympathetic neuron differentiation and their role in neuroblastoma exist for GATA3 (Almutairi 2019 ; Moriguchi 2021 ) and ASCL1 (Wang et al 2019 ; Ali et al 2020 ).…”
Section: Domains Of Progress In Understanding the Generation Specification And Connectivity Of Sympathetic Neuron Classesmentioning
confidence: 99%
“…Although initially divided into hematopoietic (GATA1/2/3) and cardiac (GATA4/5/6) GATA factors according to their functional characteristics, their functions and expression patterns far exceed these organizations, expressed in various tissues and organs. 5 In addition, several studies have found the aberrant expression of GATA transcription factors in various human malignancies, such as breast cancer, 6,7,8 urinary malignancy, 9 lung cancer, 10 pancreatic cancer. [11][12][13][14][15][16] Chang et al 13 found that GATA1 was highly expressed in pancreatic ductal adenocarcinoma and promoted pancreatic cancer gemcitabine resistance through the anti-apoptotic pathway.…”
Section: Introductionmentioning
confidence: 99%